2017
DOI: 10.1186/s12885-016-3028-0
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the Milan criteria without any sacrifice: combination of the Hangzhou criteria with the pre-transplant platelet-to-lymphocyte ratio

Abstract: BackgroundThe Hangzhou criteria expand the Milan criteria safely and effectively in selecting hepatocellular carcinoma (HCC) candidates for liver transplantation (LT), but some patients exceeding the Milan but fulfilling the Hangzhou criteria still show poor outcomes due to early tumor recurrence. In this study, the platelet-to-lymphocyte ratio (PLR) was employed to differentiate high-risk tumor recurrence recipients, and a new method combining PLR and the Hangzhou criteria was established.MethodsThe clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The Hangzhou criteria have been validated by many clinical studies in China, France, and Germany. All these studies confirmed that HCC patients who fulfill the Hangzhou criteria have achieved an acceptable post-LT 5-year survival of 72–76% and recurrence rate of 20–23% [7,2024]. In accordance with these studies, our study showed that the early recurrence rate was 15.8% with an OS rate of 71.6% for patients who met the Hangzhou criteria.…”
Section: Discussionsupporting
confidence: 88%
“…The Hangzhou criteria have been validated by many clinical studies in China, France, and Germany. All these studies confirmed that HCC patients who fulfill the Hangzhou criteria have achieved an acceptable post-LT 5-year survival of 72–76% and recurrence rate of 20–23% [7,2024]. In accordance with these studies, our study showed that the early recurrence rate was 15.8% with an OS rate of 71.6% for patients who met the Hangzhou criteria.…”
Section: Discussionsupporting
confidence: 88%
“…Of the remaining 11 papers, 6 were not considered eligible after full-text evaluation. Two studies coming from Hangzhou China were performed on the same population, so only one of these studies was selected for the last analysis[ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, this association must be taken in consideration with great caution since a moderate level of heterogeneity was found among the studies included. In a recent study by Xia et al[84], PLR failed to predict HCC recurrence in patients meeting Milan criteria, but the 5-year recurrence-free survival in patients with HCC beyond Milan criteria but within Hangzhou criteria (total tumor diameter of ≤ 8 cm or > 8 cm, well or moderately differentiated and pretransplant AFP of < 400 ng/mL and PLR < 120) was comparable to the figure for patients within Milan criteria (73.3% vs 72.8%).…”
Section: Systemic Inflammation Markersmentioning
confidence: 99%